GENERAL PRINCIPLES OF ENVIRONMENTAL POLICY IN INTERNATIONAL LAW: PRINCIPLE OF SUSTAINABLE DEVELOPMENT - Abdullaeva Ozoda Farmon qizi, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
International environmental law is underpinned by several general principles of environmental policy that guide states in developing and implementing environmental protection measures. Over the past halfcentury – from the 1972 Stockholm Conference to the 1992 Rio Earth Summit and beyond – the international community has articulated key principles to balance ecological protection with economic development. Four of the most widely recognized among these are the principle of sustainable development, the precautionary principle, the polluter-pays principle, and the principle of common but differentiated responsibilities. Each of these principles has been endorsed in global declarations and treaties and elaborated by courts and scholars in formal legal discourse. In this essay, we analyze each principle in turn, examining their origin, content, legal status, and role in international and regional practice (including perspectives from Central Asian and Uzbek scholarship), followed by a results section with visual data illustrating their application.